Skip-Correlation for Multi-Power Wireless Carrier Sensing - Bhardwaj, Romil; Chintalapudi, Krishna; Ramjee, Ramachandran (USENIX NSDI, 2017)
Carrier sensing is a key mechanism that enables decentralized sharing of unlicensed spectrum. However, carrier sensing in its current form is fundamentally unsuitable when devices transmit at different power levels, a scenario increasingly common given the diversity of Wi-Fi APs in the market and the need for Wi-Fi's co-existence with new upcoming standards such as LAA/LWA. The primary contribution of this paper is a novel carrier sensing mechanism – skip correlation – that extends carrier sensing to accommodate multiple transmit power levels. Through an FPGA based implementation on the WARP platform, we demonstrate the effectiveness of our technique in a variety of scenarios including support for backward compatibility.